Factors Influencing Success of Cadre Empowerment in Stunting Prevention in Indonesia: A Scoping Review - Wiwaha, Guswan; Husnida, Nintinjri; Adnani, Qorinah Estiningtyas Sakilah; Hilmanto, Dany (Indonesian Journal of Global Health Research, 2024)
Cadres are public health volunteers chosen from a local community. Cadres should undergo constant educational training and empowerment since they play an active role in monitoring health issues in their community, in this case stunting. The planning, implementation, and evaluation processes of cadre empowerment are not always successful and effective. This scoping review aims to identify the factors that influence the success of cadre empowerment in Indonesia, so that a model of empowerment and education can be formulated by focusing on the factors that can give the most optimal results. This scoping review is based on the guidelines of PRISMA-ScR. The article search involves two databases, PUBMED and Google Scholar. The keywords used include: Stunting [MeSH] AND “Health Cadres OR Health volunteers” AND Factors associated OR determinant. “Stunting AND Kader AND pemberdayaan AND Factor”. The review resulted in the selection of eight articles, with one focusing on a particular region of Sumatera (Aceh), while the rest are on Java (West Java, Yogyakarta, and East Java). The review finds certain shared factors that influence the success of cadre empowerment, including KAP (knowledge, attitude, and practice), self-efficacy, sectoral and community support, and resources.